EshA Accentuates ppGpp Accumulation and Is Conditionally Required for Antibiotic Production in Streptomyces coelicolor A3(2) - Saito, Natsumi (American Society for Microbiology, 2006)
Disruption of eshA, which encodes a 52-kDa protein that is produced late during the growth of Streptomyces coelicolor A3(2), resulted in elimination of actinorhodin production. In contrast, disruption of eshB, a close homologue of eshA, had no effect on antibiotic production. The eshA disruptant accumulated lower levels of ppGpp than the wild-type strain accumulated. The loss of actinorhodin production in the eshA disruptant was restored by expression of a truncated relA gene, which increased the ppGpp level to the level in the wild-type strain, indicating that the reduced ppGpp accumulation in the eshA mutant was solely responsible for the loss of antibiotic production. Antibiotic production was also restored in the eshA mutant by introducing mutations into rpoB (encoding the RNA polymerase β subunit) that bypassed the requirement for ppGpp, which is consistent with a role for EshA in modulating ppGpp levels. EshA contains a cyclic nucleotide-binding domain that is essential for its role in triggering actinorhodin production. EshA may provide new insights and opportunities to unravel the molecular signaling events that occur during physiological differentiation in streptomycetes.